Systematic Review of Emergency Department Crowding: Causes, Effects, and Solutions - Hoot, Nathan R. (Ann Emerg Med, 2008)
Emergency department (ED) crowding represents an international crisis that may affect the quality and access of health care. We conducted a comprehensive PubMed® search to identify articles that 1) studied causes, effects, or solutions of ED crowding; 2) described data collection and analysis methodology; 3) occurred in a general ED setting; and 4) focused on everyday crowding. Two independent reviewers identified the relevant articles by consensus. We applied a five-level quality assessment tool to grade the methodology of each study. From 4,271 abstracts and 188 full-text articles, the reviewers identified 93 articles meeting the inclusion criteria. A total of 33 articles studied causes, 27 articles studied effects, and 40 articles studied solutions of ED crowding. Commonly studied causes of crowding included non-urgent visits, frequent-flyer patients, influenza season, inadequate staffing, inpatient boarding, and hospital bed shortages. Commonly studied effects of crowding included patient mortality, transport delays, treatment delays, ambulance diversion, patient elopement, and financial impact. Commonly studied solutions of crowding included additional personnel, observation units, hospital bed access, non-urgent referrals, ambulance diversion, destination control, crowding measures, and queuing theory. The results illustrated the complex, multi-faceted characteristics of the ED crowding problem. Additional high-quality studies may provide valuable contributions towards better understanding and alleviating the daily crisis. This structured overview of the literature may help to identify future directions for the crowding research agenda.